2016
DOI: 10.2337/db16-0068
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lactate Concentration Falls in Response to Hypoglycemia in Patients With Type 1 Diabetes and Impaired Awareness of Hypoglycemia

Abstract: Brain lactate may be involved in the development of impaired awareness of hypoglycemia (IAH), a condition that affects approximately 25% of patients with type 1 diabetes and increases the risk of severe hypoglycemia. The aim of this study was to investigate the effect of acute hypoglycemia on brain lactate concentration in patients with IAH as compared with those with normal awareness of hypoglycemia (NAH) and healthy control subjects (n = 7 per group). After an overnight fast, all subjects underwent a two-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…In addition, the role of brain lactate to prevent seizures was reinforced by the fact that when seizures began, the brain levels of lactate in the Ins, Ins + Lac, or Ins + Glc groups were lower (p < 0.05) than those in the control group ( Figure 2H). In agreement with these results, Wiegers et al (2016) demonstrated that in type 1 diabetes patients, symptoms of insulin-induced hypoglycemia are related to the decreased availability of lactate in the brain.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the role of brain lactate to prevent seizures was reinforced by the fact that when seizures began, the brain levels of lactate in the Ins, Ins + Lac, or Ins + Glc groups were lower (p < 0.05) than those in the control group ( Figure 2H). In agreement with these results, Wiegers et al (2016) demonstrated that in type 1 diabetes patients, symptoms of insulin-induced hypoglycemia are related to the decreased availability of lactate in the brain.…”
Section: Discussionsupporting
confidence: 83%
“…A study by Wiegers et al found a decline in brain lactate concentrations in response to hypoglycemia in patients with type 1 diabetes and impaired awareness of hypoglycemia, but not in type 1 diabetic patients with normal awareness of hypoglycemia or in healthy control subjects. 14 Upon lactate infusion, Wiegers et al found only small increases in cerebral lactate concentrations during experimental hypoglycemia in patients with type 1 diabetes. 15 By contrast, data by De Feyter et al did not reveal increased lactate oxidation during hypoglycemia in type 1 diabetic subjects despite increased levels of brain lactate.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an earlier study investigated the frontal and parietal cortex, and reported no differences in metabolite levels (namely NAA/creatine and choline/creatine) between of type 1 diabetes patients with and without recurrent hypoglycaemia [32]. Recent studies reported no difference in baseline concentrations of neurochemicals in the brain of type 1 diabetes patients relative to healthy control subjects, while the brain metabolic response to hypoglycaemia may be impaired in diabetes [33,34]. In healthy subjects a hypoglycaemia insult leads to a reduction of brain glutamate levels, a response that is blunted in diabetes patients depending on their degree of hypoglycaemia-associate autonomic failure, a syndrome that includes hypoglycaemia unawareness [33,34].…”
Section: Mrs In Diabetes Patients Type 1 Diabetesmentioning
confidence: 99%
“…Recent studies reported no difference in baseline concentrations of neurochemicals in the brain of type 1 diabetes patients relative to healthy control subjects, while the brain metabolic response to hypoglycaemia may be impaired in diabetes [33,34]. In healthy subjects a hypoglycaemia insult leads to a reduction of brain glutamate levels, a response that is blunted in diabetes patients depending on their degree of hypoglycaemia-associate autonomic failure, a syndrome that includes hypoglycaemia unawareness [33,34]. In addition, brain lactate levels drop during hypoglycaemia in diabetes patients (depending on whether awareness of hypoglycaemia is impaired or not), suggesting stimulated utilisation of lactate as metabolic substrate [33,34].…”
Section: Mrs In Diabetes Patients Type 1 Diabetesmentioning
confidence: 99%